Improving medication appropriateness in nursing home residents by enhancing interprofessional cooperation: A study protocol. Issue 4 (4th July 2018) - Schaffler-Schaden, Dagmar; Pitzer, Stefan; Schreier, Magdalena; Dellinger, Johanna; Brandauer-Stickler, Beate; Lainer, Miriam; Flamm, Maria; Osterbrink, Jürgen
ABSTRACT: Polypharmacy in elderly people is an increasing challenge for health professionals. Drug-Drug interactions, dosing or administration errors can cause preventable incidents and hospitalizations. Due to chronic illness and multi-morbidity, older people are considered as a particularly vulnerable group of patients. Furthermore, it is well known that communication between health professionals is often insufficient. The aim of this study is to improve the appropriateness of medication of nursing home residents by establishing a long-term structured medication review process and to enhance the interprofessional communication between general practitioners (GPs), nurses and pharmacists. GPs review and adapt medication of residents, nurses perform structured monitoring of residents for drug-related symptoms. Pharmacists check the appropriateness of prescribed therapy by performing a medication analysis. For this purpose, a special electronic platform (SiM-Pl) is developed to extend the original health documentation system with additional tools. SiM-Pl enables participants to gain access to relevant information regardless of time and place and shall facilitate health documentation and exchange of information. All involved health professionals receive a topic-related, specific education. The study is designed as a non-randomized, controlled trial. Health-related benefits and improved quality of life are expected for the participating residents.